Scientific eventuality or science fiction: The future of people with different abilities. (March 2017) - Bennett, DeeDee
Highlights: This explores how the perception of disability may be culturally transformed from disabilities to differing abilities. The author conceptualizes a way to influence current innovators to universally design the wireless technologies of the future. By influencing the cyberpunk subgenre of science fiction, the author suggests a way to shift societal culture of disability. The author visualizes how the perception of disability may be transformed from (dis)abilities to recognizing differing abilities. This paper reveals that a cultural perception change will also cause a significant shift in policy and ethical considerations in the future. Abstract: Consider this, we are living in a future [in-part] imagined over 30 years ago- in science fiction film and books. We may envision that 30 years from now we could live in a future with technology developed from the concepts we see in science fiction today. In this paper, the concepts of disability are challenged in the future based on the technologies imagined in the science fiction genre of the present and past. Focused on the sub-genre, Cyberpunk, current mainstream, as well as new emerging technologies inspired by science fiction are reviewed. Future disability is reimagined dependent on continued support and acceptance of the emerging technology. If our past is any indication, our future may lie in the conceptual and slightly implausible figments of our science fiction-based imaginations. However, the cultural shift will significantly impact our laws, regulations, and policies, as well as introduce new societal concerns.